Principio de capacidad contributiva y su efecto en el cálculo del impuesto a la renta de las personas naturales de la ciudad de Chimbote, 2013 - Armas Dávila, Yolvy César (2016)
He purpose of the research was to determine the effect of the ability to pay in calculating the income tax of natural persons in the city of Chimbote, 2013. The principle of ability to pay originates in the economic capacity of the taxpayer, since it is the basis and sustenance of taxation. In addition, because only by law is obliged to contribute to public expenditure, and not through the enjoyment of the public services provided by the state. We worked with a universe - sample of 120 individuals, which were selected by probalistico not being used at the discretion of the investigator the technique of sampling survey. Also analíticos- synthetic methods used, inductivos- inferential statistical. It concludes that the principle of ability to pay does not protect the family unit because it taxes income without examining the condition; so it is not considered family burden the taxpayer. It is recommended that the Tax Administration must unify criteria and create a tax concept governing the tax system, which refers to the taxpaying capacity as its defining element is made and give up the idea of consideration.